Problematika Penurunan Karakter Perempuan di Era Globalisasi: Telaah Surat An-Nur Ayat 31 dan An-Nisa Ayat 34 - Abdullah Aziz; Tulus Musthofa; Nur Saidah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Women today have found their identity as women. In the jahiliyyah era, women were considered useless, weak, and only as slaves to satisfy men. But now women have gotten their rights with gender equality. Women have been involved in contributing in all fields ranging from education, economy, social, politics and other fields. As time goes by, now the era is transforming into an era of globalization that gets a lot of benefits and conveniences. But on the other hand, women today have shown a decline in morals due to the impact of globalization which can be seen from the loss of shame, saying rude words, exposing the aurat, wearing westernized clothes, disobeying husbands and others. This is a very troubling phenomenon. This study uses the library research method in finding existing sources both from journals and books in accordance with the review in terms of aspects of character, women, education, Qur'anic verses relevant to this study by using data analysis techniques, namely content analysis